Example: Simplify the expression given below,

3x+4y+3z +8 +4x +4y +4z +6 – 4x -3y -3z +4?

Solution: We can make own rules to simplify this type of expression,

First we will add the constant containing ‘x’ with each other so we will get the result as

3x+ 4x - 4x,

4x will get cancel out with 4x and we will get the result as 3x.

Now we will add the term containing ‘y’ with each other so we will get,

= 4y + 4y -3y,

= 8y-3y,

= 5y,

Now we will add the term containing ‘z’ with each other so we will get,

=3z + 4z – 3z,

=7z-3z,

= 4z.

Now we will add the constants,

= 8+6 +4,

= 18.

Now we can rewrite the given equation as

3x + 5y + 4z +18,

As you can see by applying simple rules we minimized our expression, we can't minimize the expression any more, we can minimize it only if we are having the value of variables.

In this way we can simplify our expression and we will get the desired result.